Epidemiological profile of patients with stroke sequelae attended at a rehabilitation center in Lima-Peru - Urcia-Fernández, Fernando (2023)
Objective: To describe the epidemiologic profile of patients with cerebrovascular accidents (CVA) attended at a rehabilitation center in Lima-Peru. Methods: A cross-sectional study was carried-out at Instituto Nacional de Rehabilitación “Dra. Adriana Rebaza Flores” AMISTAD PERÚ-JAPÓN from 2013 to 2019. Information on sociodemographic, clinical, chronic underlying conditions and use of illicit drugs and medications were gathered. Results: 71.5% of our patients had ischemic CVAs and 87.6% had moderate to severe sequalae. Higher frequency of sequalae due to ischemic CVAs was found among people older than 56 years of age (80.7%), while sequalae of hemorrhagic CVAs was found predominantly above 46 years of age (61.8%). Hemiplegia was found in 81.7%; 58% had verbal communication problems; 2.1% had audition problems; 67.3% had blood hypertension and 16.1% had history of tobacco consumption. Most of the patients with any degree of sequalae were either married or cohabitant. The higher the severity of sequalae, higher percentage of old illiterate females. Conclusions: Most of the patients with CVAs had moderate-severe sequalae including hemiplegia, verbal communication problems and blood hypertension. Patients with ischemic CVAs were older than those with hemorrhagic CVAs. The higher the severity of sequalae, higher percentage of old illiterate females.